Endovascular treatment of peripheral arterial injury with covered stents: an experimental study in pigs - Sergio Belczak; Erasmo Simião da Silva; Ricardo Aun; Igor Rafael Sincos; Alessandro Rodrigo Belon; Ivan Benaduce Casella; Vitor Gornati; Luiz Francisco Poli de Figueiredo (Clinics, 2011)
OBJECTIVE: To evaluate the feasibility of using endovascular repair to treat penetrating arterial injuries with covered stents. Feasibility was examined according to the circumferential extent of the injury. INTRODUCTION: Surgical trauma often increases the risk of major morbidity and mortality associated with vascular injury, and endovascular repair has many advantages in such situations. METHODS: Twenty white male domestic pigs weighing 28-38 kg with controlled vascular injuries were divided into four equal groups according to the circumferential extent of their vascular lesion (i.e., no lesion, lesion <50%, lesion >50%, and complete lesion). The left common carotid artery was dissected with proximal and distal control, and this procedure was followed by controlled sectioning of the arterial wall. Local manual compression was applied for 10 min and was followed by endovascular repair with the placement of a 5x50 mm VIABHAN TM covered stent using the femoral approach. We also monitored additional variables, such as the duration of the procedures (the mean was 56.3 ± 19.1 min), ultrasound parameters (e.g., maximum arterial diameter, peak systolic and diastolic velocity, and resistance index), arteriography findings, and fluctuations in vital signs (e.g., cardiac output, arterial pressure, and central venous pressure). RESULTS: The experimental procedure was found to be feasible and reproducible. Repairs were successful in all animals in the control (no lesion) and <50% lesion groups. Success was also achieved in four out of five pigs in the >50% group and in one pig in the complete lesion group. DISCUSSION: The endovascular repair of an arterial injury is possible, but success depends on the circumferential extent of the arterial lesion. The present experimental model, which involved endovascular techniques, highlighted important factors that must be considered in future studies involving similar animals and materials.